Widening the landscape of education design: from a teaching model to a functional model - Vercesi, Paolo (Formazione & insegnamento, 2019)
Alongside the digitalization of processes, the ongoing transformations within the productive sectors and the changes occurring in the organization of the society, despite the shared perception of the relevance of innovation in every policy area, an approach to education basing its design on an advanced, flexible, consistent operating model, able to adjust to the continuous and ever faster transformations in the economic and social system, is yet to be foreseen. Following the experiences and contexts analysis, the proposal is based on the conviction that the innovations which have been described, even though they are necessary and, in a way, compelling, cannot be pursued only by exploiting the models and structures which are today intended for education and training, not even by introducing them to some incremental changes. Experience leads one to think that there is a need for a rearrangement of the work processes, of the structures and duties of the staff working in the education system (i.e. teachers, secretaries, service personnel, headmasters) which is, rearrangement at the same time combined with a new organization of the educational contents related to the update and acquisition of skills and to the innovation of the digital tools to access them. Thus, digital technologies would no longer simply be and efficient way to improve current activities, but they would become a strategic tool to start a processes reengineering.